Infrastructure Development in the UK: Key Drivers and Implementation Challenges - Rafiu Dimeji Seidu; Herbert Robinson; Bert Ediale Young; Michael Ryan; Daniel Fong (Journal of Infrastructure Policy and Management (JIPM), 2023)
Infrastructure is a critical factor in fostering strong and sustained economic growth, hence, sufficient attention should be given to the allocation of investment. Although UK infrastructure investment have risen in line with the global trend, the level of investment remains in the lower percentile when compared to other leading countries such as Singapore and China. The study examines the challenges of infrastructure development in the UK and explored the policies required to stimulate investment. Using semi-structured interviews, the views of key stakeholders involved in infrastructure operating across key sectors of transport and energy were captured to gain an insight into the key policy drivers of infrastructure investment. Findings from the research suggests that policy changes are required to stimulate significant investment if the UK is to become a world leader in infrastructure. Key criticisms of UK infrastructure policy focussed on comparatively low level of investment, inadequate collaboration between key stakeholders, and the regional bias of investment in favour of London which disproportionately affects the Northern regions. To facilitate economic growth, the identification of future investible pipeline of infrastructure projects, increasing collaboration with local stakeholders and addressing the regional biases will be critical to ensure synergy and ownership and to scale up the implementation of UK future infrastructure development plans. Considerations should also be given to the need to set up infrastructure banks similar to what is in operation in other countries such as China and Singapore to stimulate private investment and to complement public sector budget allocations. Improving infrastructure project implementation through institutional coordination will boost economic growth post Brexit, support the development of new trading agreements and enhance the country’s economic performance after the pandemic